Seismic signatures of siliciclastic reservoirs as function of burial history - a Barents Sea example. - Guldbrandsøy, Petter Næss (The University of Bergen, 2017)
The Barents Sea is one of the most exciting areas regarding oil and gas exploration at the Norwegian Continental Shelf. Compared to the North Sea the area has a complex burial history, making the exploration challenging. One major challenge is the understanding of elastic properties and the coherent seismic signatures during the history. In this study, the seismic signatures are discussed. To be able to do this it is first necessary to establish a good geological model, and then use different rock physics models to look at elastic properties at various stages during history. A published geological burial history for the Bjarmeland Platform is extended and used as a reference for the rock physics modeling. Different rock physics models have been used to predict the elastic properties for changes in pressures, temperatures, and for cementation and formation of cracks during the burial and uplift. Also, a fluid substitution model is used to predict saturation effects. The amplitude versus offset (AVO) modeling is done using simplistic methods for AVO-intercept and -gradient, based on the rock physics modeling. The study shows that the major changes in elastic properties during a burial history are caused by cementation and fluid substitution. There are several minor changes as well, like increased pressure, temperature and uplift. Still, they are insignificant compared to the cementation and fluid substitution. Therefore, the most important part of the burial history, in this study, is the maximum burial depth in combination with the geothermal gradient. These components are important to understand if the reservoir has been cemented in the chemical compaction domain at some point in the history. Seismic attributes are discussed using the calculated gradient and intercept for the elastic properties at various stages in the burial history. It is shown that the biggest changes in AVO are caused by the cementation and fluid substitution. Also, it has been demonstrated how cracks move the AVO-response in the opposite ...